The Base of Prosperity in Developing Economies: A Case of Business Enterprises in Nepal - K.C., Jit Bahadur (Pravaha, 2020)
Purpose: This article aims to explain the status of BEs and to discuss their role in Nepal for a prosperous nation. Methods and materials: The study adopts the explanatory methods using both (i.e., primary and secondary) source and secondary data. For this purpose, the study entertained the process of collecting, arranging, organising and interpreting the collected data with appropriate forms. Findings and conclusion: The study found different types and forms of BEs in Nepal with different legal statuses but very small in number. The forms of BEs showed that sole proprietorship and P.Ltd. dominated business culture. Foreign companies and public limited companies which issue shares and debentures found in nominal number. The conclusion of the study shows that the governments of Nepal from the very beginning have not been working in a planned way to established the BEs in the appropriate required forms, types, natures and manner. Considering the requirement of the nation on the BEs, the government of Nepal should immediately take a good step for further development of the BEs. Originality/value: In this subject and context it is the first attempt although it deals with the BEs with different aspects and explains the role of BEs for the prosperity of the nation very clearly and substantially. However, it requires further study to be completed in all aspects.